Gene Atlasing of digestive and reproductive tissues in Schistosoma mansoni. - Sujeevi S K Nawaratna; Donald P McManus; Luke Moertel; Geoffrey N Gobert; Malcolm K Jones (Public Library of Science (PLoS), 2011)
BACKGROUND: While considerable genomic and transcriptomic data are available for Schistosoma mansoni, many of its genes lack significant annotation. A transcriptomic study of individual tissues and organs of schistosomes could play an important role in functional annotation of the unknown genes, particularly by providing rapid localisation data and thus giving insight into the potential roles of these molecules in parasite development, reproduction and homeostasis, and in the complex host-parasite interaction. METHODOLOGY/PRINCIPAL FINDINGS: Quantification of gene expression in tissues of S. mansoni was achieved by a combination of laser microdissection microscopy (LMM) and oligonucleotide microarray analysis. We compared the gene expression profile of the adult female gastrodermis and male and female reproductive tissues with whole worm controls. The results revealed a total of 393 genes (contigs) that were up-regulated two-fold or more in the gastrodermis, 4,450 in the ovary, 384 in the vitelline tissues of female parasites, and 2,171 in the testes. We have also supplemented these data with the identification of highly expressed genes in different regions of manually dissected male and female S. mansoni. Though relatively crude, this dissection strategy provides low resolution localisation data for critical regions of the adult parasites that are not amenable to LMM isolation. CONCLUSIONS: This is the first detailed transcriptomic study of the reproductive tissues and gastrodermis of S. mansoni. The results obtained will help direct future research on the functional aspects of these tissues, expediting the characterisation of currently unannotated gene products of S. mansoni and the discovery of new drug and vaccine targets.